2017
DOI: 10.1113/jp273871
|View full text |Cite
|
Sign up to set email alerts
|

Leg vascular and skeletal muscle mitochondrial adaptations to aerobic high‐intensity exercise training are enhanced in the early postmenopausal phase

Abstract: Exercise training leads to favourable adaptations within skeletal muscle; however, this effect of exercise training may be blunted in postmenopausal women as a result of the loss of oestrogens. Furthermore, postmenopausal women may have an impaired vascular response to acute exercise. We examined the haemodynamic response to acute exercise in matched pre- and postmenopausal women before and after 12 weeks of aerobic high intensity exercise training. Twenty premenopausal and 16 early postmenopausal (mean ± SEM:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 60 publications
3
50
2
1
Order By: Relevance
“…A similar pattern was observed for infusion of acetylcholine, although the difference between the 2 groups at baseline was smaller. Exercise training improved the amount of eNOS and cyclooxygenase in the muscle of the post‐menopausal women . This finding is in congruence with reports of training‐induced increases in eNOS in ovariectomized animals .…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…A similar pattern was observed for infusion of acetylcholine, although the difference between the 2 groups at baseline was smaller. Exercise training improved the amount of eNOS and cyclooxygenase in the muscle of the post‐menopausal women . This finding is in congruence with reports of training‐induced increases in eNOS in ovariectomized animals .…”
Section: Introductionsupporting
confidence: 89%
“…In endothelial cells from internal mammary artery of post‐menopausal women, eNOS expression is reduced compared to endothelial cells from pre‐menopausal women, and hormone replacement therapy has been shown to increase circulating levels of NO metabolites in post‐menopausal women, suggesting that chronic changes in estrogen levels have implications for the NO system. On the other hand, the protein content of eNOS and prostacyclin synthase in whole muscle homogenate from pre‐ and early post‐menopausal women do not seem to differ . This inconsistency could be linked to the smaller age difference between the pre‐ and post‐menopausal women in the latter study …”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In support of this theory, it has been shown that a period of exercise training increases the expression of ERRα in recent postmenopausal women, but not in premenopausal women, in parallel with a greater increase in the eNOS expression in the recent postmenopausal women, suggesting that activation of the ERRα pathway is of greater importance for the training adaptations in the recent postmenopausal group and that the presence of oestrogen in the premenopausal group may limit the ERRα pathway (Nyberg et al . ). Unpublished observations from our lab also indicate that the expression of ERRα is reduced as a function of years after menopause in sedentary women (see Fig.…”
Section: Introductionmentioning
confidence: 97%